Artificial nitrogen fixation over bismuth-based photocatalysts: fundamentals and future perspectives. Issue 10 (26th February 2020) - Huang, Yewei; Zhang, Nan; Wu, Zhenjun; Xie, Xiuqiang
Abstract : Fundamentals and future perspectives on artificial N2 fixation over bismuth-based photocatalysts have been discussed. Abstract : Ammonia, one of the most basic substances in modern organic synthesis, is not only of great significance to human society, but also the backbone on which earth's life depends. Photocatalysis potentially provides a sustainable ammonia production technology as an alternative to the traditional Haber–Bosch process, and has been attracting extensive research interest recently. The development of efficient photocatalysts remains one of the fundamental issues for boosting the solar-to-ammonia efficiency. Significant and fruitful research on bismuth-based photocatalysts for nitrogen fixation to ammonia has been reported in recent years. This review summarizes and discusses recent advances in photocatalytic nitrogen fixation to ammonia over bismuth-based semiconductors. The fundamentals of solar-to-ammonia conversion and reported methods for ammonia quantification are introduced, together with a specific focus on strategies to enhance the performances of bismuth-based photocatalysts for nitrogen fixation. Finally, we cast a personal prospect on the future development of this vibrant research area, by which we hope to provide a useful scaffold for future research for the rational design of efficient bismuth-based photocatalysts for sustainable ammonia production.